Mutational Landscape of Pirin and Elucidation of the Impact of Most Detrimental Missense Variants That Accelerate the Breast Cancer Pathways: A Computational Modelling Study - Suleman, Muhammad; Tahir ul Qamar, Muhammad; Saleem, Shoaib; Ahmad, Sajjad; Ali, Syed Shujait; Khan, Haji; Akbar, Fazal; Khan, Wajid; Alblihy, Adel; Alrumaihi, Faris; Waseem, Muhammad; Allemailem, Khaled S. (Frontiers in Molecular Biosciences, 2021)
Pirin (PIR) protein is highly conserved in both prokaryotic and eukaryotic organisms. Recently, it has been identified that PIR positively regulates breast cancer cell proliferation, xenograft tumor formation, and metastasis, through an enforced transition of G1/S phase of the cell cycle by upregulation of E2F1 expression at the transcriptional level. Keeping in view the importance of PIR in many crucial cellular processes in humans, we used a variety of computational tools to identify non-synonymous single-nucleotide polymorphisms (SNPs) in the PIR gene that are highly deleterious for the structure and function of PIR protein. Out of 173 SNPs identified in the protein, 119 are non-synonymous, and by consensus, 24 mutations were confirmed to be deleterious in nature. Mutations such as V257A, I28T, and I264S were unveiled as highly destabilizing due to a significant stability fold change on the protein structure. This observation was further established through molecular dynamics (MD) simulation that demonstrated the role of the mutation in protein structure destability and affecting its internal dynamics. The findings of this study are believed to open doors to investigate the biological relevance of the mutations and drugability potential of the protein.